Theory and Practice in Criminal Law - Bossowski, Józef Jan (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Teoria i praktyka w prawie karnym by Józef Jan Bossowski published originally in Polish in “Ruch Prawniczy, Ekonomiczny i Socjologiczny” in 1924. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz Uniersity, Poznań.